2021
DOI: 10.36984/jkm.v4i2.240
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Terapi Bermain Puzzle Terhadap Kecemasan Pada Anak Pra Sekolah

Abstract: Sebagian besar anak-anak yang mengalami perawatan di rumah sakit merasakan kecemasan. Masih tingginya angka kesakitan pada anak tentunya akan berdampak terhadap rasa takut dan cemas pada anak jika anak dirawat  di  rumah  sakit.  Untuk mengurangi  kecemasan  pada  anak  dilakukan  terapi  bermain  puzzle. Tujuan penelitian  ini adalah  untuk mengetahui  pengaruh terapi bermain puzzle terhadap kecemasan pada anak pra sekolah (3-6 tahun). Jenis penelitian menggunakan desain penelitian quasi ekperimen dengan meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
2
0
4
Order By: Relevance
“…Based on the results of research conducted by [7], the results of this study found that children's anxiety appeared to decrease after being given puzzle play therapy for 15 minutes with an average anxiety value before being 76.2 and after giving puzzle therapy to children. Pre-school there was a decrease in anxiety levels with a value of 42.6 and there was a significant difference in anxiety before and after being given puzzle therapy to pre-school children with an average difference in anxiety of 33.6 [8].…”
Section: Results Of Analysis Of the Implementation Of Anxiety Reducti...mentioning
confidence: 87%
See 1 more Smart Citation
“…Based on the results of research conducted by [7], the results of this study found that children's anxiety appeared to decrease after being given puzzle play therapy for 15 minutes with an average anxiety value before being 76.2 and after giving puzzle therapy to children. Pre-school there was a decrease in anxiety levels with a value of 42.6 and there was a significant difference in anxiety before and after being given puzzle therapy to pre-school children with an average difference in anxiety of 33.6 [8].…”
Section: Results Of Analysis Of the Implementation Of Anxiety Reducti...mentioning
confidence: 87%
“…According to Gupta et al, (2018) explained that there is an influence of therapeutic play (puzzles) on the anxiety level of pre-school aged children undergoing hospitalization in hospital [12]. Therapeutic play using puzzles can reduce anxiety levels in pre-school children undergoing hospitalization [7].…”
Section: Results Of Analysis Of the Implementation Of Anxiety Reducti...mentioning
confidence: 99%
“…Terapi bermain merupakan metode yang paling tepat diterapkan pada anak karena aktivitas bermain tidak bisa dilepaskan dari dunia anak. Manfaat terapeutik lain dari terapi bermain adalah anak mampu mengeksplorasikan perasaan, melepaskan ketegangan atau kecemasan (Sapardi & Andayani, 2021). Evaluasi setelah lima hari dari hasil observasi kontak mata ada, anak berespon terhadap lawan bicara dan mulai melakukan aktivitas tata cara dan mandi secara perlahan.…”
Section: Pembahasanunclassified
“…Pentingnya terapi bermain juga mencakup peranannya dalam mendukung perkembangan sosial-emosional anak pra sekolah. (Sapardi & Andayani, 2021)…”
Section: Pembahasanunclassified